Do socio-demographic factors still predict the choice of place of delivery: A cross-sectional study in rural North India - Jyotiranjan Sahoo; Satya Vir Singh; Vimal Kishore Gupta; Suneela Garg; Jugal Kishore (Springer, 2015)
Improving maternal health is one of the goals to be achieved under the Millennium Development Goal (MDG), especially MDG-5. One of the predictors of maternal health is place of child birth. This study was carried out to determine the prevalence of home delivery and different socio-demographic factors associated with them. This study was a community-based cross-sectional study. Women who delivered a baby in the past 1 year were included in this study. A total of 300 women responded (93.2%) and gave consent to participate in the study. Prevalence of home delivery was 37.7%. Bivariate analysis showed that religion, caste, education of women and their partners, occupation of the spouse, monthly family income and socioeconomic status had a significant association with the choice of place of delivery. But multivariate regression analysis showed only religion, caste, education of spouse and monthly income to be significant factors in determining place of delivery. The findings of this study suggest that individual countries have to formulate interventions which will target marginalized or vulnerable populations with reference to caste, religion and wealth. A significant improvement in reaching the 5th MDG can be achieved if the first three MDG goals are focused on, i.e., eradication of poverty, achieving universal education and women empowerment.